Factorization Conjecture and Open/Closed String Correspondence - SHATASHVILI, SAMSON (My University, 2005)
We present evidence for the factorization of the world-shee t path integrals for 2d con- formal field theories on the disk into bulk and boundary contr ibutions. This factorization is then used to reinterpret a shift in closed string backgrou nds in terms of boundary de- formations in background independent open string field theo ry. We give a proof of the factorization conjecture in the cases where the background is represented by WZW and related models
PUBLISHED
Keywords: Chemistry